Long-Term Follow-Up of Vestibular Function in Cochlear-Implanted Teenagers and Young Adults - Niki Karpeta; Eva Karltorp; Luca Verrecchia; Maoli Duan (Audiology Research)
Background: Vestibular function implements head position regulation and body spatial navigation. It matures during childhood and adolescence and integrates with the completion of an individual’s motor development. Nevertheless, vestibular impairment is associated with profound paediatric hearing loss and has a negative impact on the child’s motor proficiency. Cochlear implantation (CI) is the treatment of choice for severe hearing loss, where conservative treatment plans are not appropriate or fail. The Teenager and Young Adults Cochlear Implant (TAYACI) study investigates the long-term outcomes of early implantation with respect to the hearing, speech, psychological, and balance development among CI users. Methods: This study focuses on the vestibular function and the appropriate methods for vestibular assessment. The results of two established vestibular test methods are explored: the video head impulse test (vHIT) and cervical/ocular vestibular-evoked myogenic potentials (cVEMP, oVEMP) with air and bone conduction vibration stimulation. The results of vHIT, cVEMP, and oVEMP, per implanted ear and the relation to the aetiology of hearing loss are reported. An additional dynamic visual acuity (DVA) test was included to assess clinical oscillopsia. Results: Overall abnormal lateral canal testing was detected in 35/76 (46.1%) of the implanted ears. Bone-conducted cVEMP (BC cVEMP) was pathological in 33/76 (43.3%) and BC oVEMP in 42/76 (55.3%). Lateral canal impairment was associated with the background diagnosis of the hearing loss. Oscillopsia was related to bilateral canal impairment (sensitivity 73% specificity 100%). Conclusions: Lateral canal testing together with BC VEMPs were the most reproducible modules for vestibular testing The above tests were related to each other and complemented the overall vestibular assessment. DVA is a helpful tool to screen dynamic oscillopsia in patients with bilateral vestibular impairment.